Amino Acid Composition Of The Ripe Fruits Of Solanum Aethiopicum And Solanum Macrocarpon - E.I. ADEYEYE,; I.G. ADANLAWO, (International Journal of Pharma and Bio Sciences, 2011)
The two horticulturally important eggplant species with an African ancestry are the scarlet eggplant, Solanum aethiopicum and gboma eggplant, Solanum macrocarpon L. The amino acid composition of the fruits of Solanum aethiopicum and Solanum macrocarpon was determined on dry weight basis. The total essential amino acid ranged from 288 g kg-1 to 318 g kg-1 crude protein or from 48.9 % to 50.3 % of the total amino acid. The two samples had high correlation coefficient (rxy = 0.9876). The predicted protein efficiency ratio was 1.90 - 2.30, essential amino acid index range was 0.81-0.90 and the lysine amino acid score based on whole hen’s egg was 0.54-0.61. The quality of protein was high. Among the 17 amino acids determined, the S. macrocarpon was more concentrated in 15 (88.2 %) than the S. aethiopicum; the other two were the acidic amino acids (Asp and Glu).